2021
DOI: 10.4269/ajtmh.21-0081
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection in Ivory Coast: A Serosurveillance Survey among Gold Mine Workers

Abstract: Of the 107 million COVID-19 cases worldwide, less than 2 million have been reported in African countries. The aim of this study was to evaluate the seroprevalence of SARS-CoV-2 infection in Ivory Coast mine workers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 8 publications
2
18
0
2
Order By: Relevance
“…data, https://doi.org/10.1101/2020.08.04.20168112 ). Similarly, seroprevalence was 40% in public sector patients in Cape Town, South Africa ( 14 ), 12.3% among asymptomatic healthcare workers in Blantyre, Malawi ( 12 ), and 25.1% among gold mine workers in Côte d’Ivoire ( 15 ). In Addis Ababa, Ethiopia, seroprevalence among those reporting no close contact with SARS-CoV-2 infected persons was 8.8% in April 2020 (B.N.…”
Section: Discussionmentioning
confidence: 99%
“…data, https://doi.org/10.1101/2020.08.04.20168112 ). Similarly, seroprevalence was 40% in public sector patients in Cape Town, South Africa ( 14 ), 12.3% among asymptomatic healthcare workers in Blantyre, Malawi ( 12 ), and 25.1% among gold mine workers in Côte d’Ivoire ( 15 ). In Addis Ababa, Ethiopia, seroprevalence among those reporting no close contact with SARS-CoV-2 infected persons was 8.8% in April 2020 (B.N.…”
Section: Discussionmentioning
confidence: 99%
“…Studies among blood donors in Kenya and South Africa from April to June 2020 report anti-SARS-CoV-2-IgG seroprevalence of, respectively, 4.5% nationally [17] and 60% among South African black populations, seven times that of in-country white populations [18]. Two studies reported SARS-CoV-2-IgG positivity of 23.7% in workers of low socio-economic status in Cape Town, South Africa [19], and 25.1% in gold mine workers and administrative staff in Ivory Coast [20]. These studies collected blood samples between April and October 2020 during the first wave of the COVID-19 spread throughout the continent, with the second wave largely peaking around December 2020 [21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies among blood donors in Kenya and in South Africa from April to June 2020 report anti-SARS-CoV-2 IgG seroprevalence of, respectively, 4.5% nationally 17 and 60% among South African black populations, seven times that of in-country white populations 18 . Two studies reported SARS-CoV-2-IgG positivity of 23.7% in workers of low socio-economic status in Cape Town, South Africa 19 and 25.1% in gold mine workers and administrative staff in Ivory Coast 20 . These studies collected blood samples between April and October 2020, during the first wave of COVID-19 spread throughout the continent, with the second wave largely peaking around December 2020 21 .…”
Section: Introductionmentioning
confidence: 99%